Pengaruh Kualitas Pelayanan Terhadap Kinerja Keuangan Dengan Loyalitas Nasabah Sebagai Variabel Intervening (Studi Pada Perusahaan Perbankan 2011-2012) - Aminatuzzuhro Aminatuzzuhro (e-Jurnal Kewirausahaan, 2014)
Researchinaccountingsupport measuresnon-financialperformance of the company, such asservice qualityandcustomerloyalty, asa useful indicatorasaspects ofcorporate performance. The researchgoalis to provide amodel ofthe effectof service quality onfinancial performance(ROA) withcustomerloyaltyas an intervening variablein thebankingindustryinIndonesia. The resultis a developmentof thepreviousaccountingresearchIttner &Larcker, (1998)and SmithandWright(2004). Research dataused inthis study were: (1) indexservicetocareas aproxyofservice quality, sourcedfroma survey conductedbyMarkPlusInsightonthe indexservicetocare. (2) loyaltyindexas a proxy ofcustomerloyalty, derivedfrom therelease ofthe results ofthe surveyonMarkPlusInsight IndonesianbankLoyalty Index(IBLI). (3) The financial statementsof banks tocalculateROApublication. Objectsdefinedinthis study is atbest10conventional bankswithassets aboveRp75trillionand10conventionalbankswithassets ofless than Rp75trillionforthe period 2011-2012. The results showedthat: 1) Quality of carewas nota significantinfluenceon customer loyaltywitha significantlevel of0.714. 2) Customer loyaltysignificant effect onfinancialperformance(ROA), a significantlevel of0.002. 3) Quality of serviceis nota significanteffectonfinancialperformance(ROA) with asignificantlevel of0.677. 4) quality of serviceandcustomerloyaltysimultaneouslysignificant effect onfinancial performance(ROA) witha significantvalue of0.007. Keywords: Service QualityBank; CustomerLoyalty, Financial Performance(ROA)